The Effect of Investment Knowledge, Minimum Capital, Motivation on Student Interest in Investing in the Sharia Capital Market - Intan Sari Tanjung; Andri Soemitra; Budi Dharma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The research aims to examine the effect of Investment Knowledge, Minimum Capital, and Motivation on Student Interest in Investing in the Islamic Capital Market. This research method is a quantitative method with a descriptive approach, this research approach produces a population of 429 with a sample of 71. The data collection method used in this research is a questionnaire. The result of calculating the t-value is 2.890. We can conclude that (X1) has a significant impact on (Y) because this value is greater than ttable (1.465) and the sig value is less than 0.05. So, it is concluded that (X1) has a significant effect on (Y). At the sig value or t value Variable (X2) has a t value = 2.532. This value is greater than the t table (1.465) with a sig value (0.00001 <0.05). (X2) has an effect on (Y). The variable (X3) has a calculated t value = 2,935. This value is greater than the t table (1.465) with a sig value (0.005 <0.05). (Y) is influenced by the variable (X3). Based on the calculation results above, it can be seen that F count (25.308) which is greater than F table (3.08), and Sig F (0.000b) which is less than 5% (0.050) indicates that together the variable (X) has a simultaneous effect on (Y).